Millie Cooper's ride a true story from history - Simmons, Marc; Kil, Ronald R. 1959- (Albuquerque University of New Mexico Press, 2002)
During the War of 1812, when settlers at Fort Cooper, Missouri, are besieged by a coalition of Indian nations allied with the British, twelve-year-old Millie volunteers to ride to nearby Fort Hempstead for reinforcements.
81310
Keywords: Cooper, Millie -- Juvenile fiction; Indians of North America -- Fiction; United States -- History -- War of 1812 -- Juvenile fiction; Missouri -- History -- 19th century -- Fiction